Macrophage activation syndrome: a potentially fatal complication of rheumatic disorders. Issue 5 (1st November 2001) - Sawhney, S; Woo, P; Murray, K J
Abstract : AIMS: To review the precipitating events, clinical features, treatment, and outcome of macrophage activation syndrome (MAS). METHODS: Retrospective review of cases of MAS from a prospectively collected database of children with rheumatic diseases from 1980 to 2000. RESULTS: Nine patients (eight girls) were considered to have evidence of MAS. The primary diagnosis was systemic onset juvenile idiopathic arthritis in seven, enthesitis related arthritis in one, and chronic infantile neurological cutaneous articular syndrome in one. Mean age of onset was 5.7 years, and duration prior to MAS, 4.2 years. No medication was identified as a trigger. Eight had infections prior to MAS; specific infectious agents were identified in four. High grade fever, new onset hepatosplenomegaly, and lymphadenopathy were common clinical features. Platelet counts fell dramatically, from an average of 346 to 99 × 10 9 /l. Mean erythrocyte sedimentation rate (in three patients) fell from 115 to 28 mm/h. Eight had abnormal liver function during the disease course, and six had coagulopathy. Bone marrow examination supported the diagnosis with definite haemophagocytosis in four of seven. All received high dose steroids (eight intravenous, one oral), five cyclosporin, two cyclophosphamide, and one antithymocyte globulin. Two of three patients with significant renal impairment died. CONCLUSION: MAS is a rare and potentially fatal complication of childhood rheumatic disorders. Most of our patients were female, and most cases were preceded by infection. Bone marrow studies support the diagnosis. Deranged renal function may be a poor prognostic sign. Aggressive early therapy is essential.